2021
DOI: 10.3390/ma14040707
|View full text |Cite
|
Sign up to set email alerts
|

Fly Ash with Ammonia: Properties and Emission of Ammonia from Cement Composites

Abstract: The article presents the results of tests performed on fly ash with a high content of ammonium (up to 400 ppm) from the NOx reduction process. The main properties of fly ash were tested according to EN 450-1 and the results were compared with fly ash without ammonium. The comparison showed that fly ash with high concentration of ammonium suits the requirements of the European standard. Although the requirements do not limit the ammonium content, using such material as an additive for cement composites causes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…5. The method of preparing samples for testing and the techniques used during microstructural analyses using scanning microscopy were similar to those described in earlier publications [72,73].…”
Section: Resultsmentioning
confidence: 99%
“…5. The method of preparing samples for testing and the techniques used during microstructural analyses using scanning microscopy were similar to those described in earlier publications [72,73].…”
Section: Resultsmentioning
confidence: 99%
“…As the results of a spill test confirmed, the addition of fly ash affects the workability and also mortar thickening occurs. During mixture mixing, a reaction of ammonia compounds with alkalis and releasing of NH3 occurs, product [18]. The bulk density of the reference sample was determined around 2.050 kg/m 3 .…”
Section: Alkali Activated Bindermentioning
confidence: 99%
“…As a result, the problem of the utilization of denitrified fly ash is becoming more and more common in concrete. A large number of studies have shown that NH 4 HSO 4 is a by-product of denitrified fly ash [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%